Metabolic specialization of denitrifiers in permeable sediments controls N2O emissions. (16th October 2018) - Marchant, Hannah K.; Tegetmeyer, Halina E.; Ahmerkamp, Soeren; Holtappels, Moritz; Lavik, Gaute; Graf, Jon; Schreiber, Frank; Mussmann, Marc; Strous, Marc; Kuypers, Marcel M. M.
Summary: Coastal oceans receive large amounts of anthropogenic fixed nitrogen (N), most of which is denitrified in the sediment before reaching the open ocean. Sandy sediments, which are common in coastal regions, seem to play an important role in catalysing this N‐loss. Permeable sediments are characterized by advective porewater transport, which supplies high fluxes of organic matter into the sediment, but also leads to fluctuations in oxygen and nitrate concentrations. Little is known about how the denitrifying communities in these sediments are adapted to such fluctuations. Our combined results indicate that denitrification in eutrophied sandy sediments from the world's largest tidal flat system, the Wadden Sea, is carried out by different groups of microorganisms. This segregation leads to the formation of N2 O which is advectively transported to the overlying waters and thereby emitted to the atmosphere. At the same time, the production of N2 O within the sediment supports a subset of Flavobacteriia which appear to be specialized on N2 O reduction. If the mechanisms shown here are active in other coastal zones, then denitrification in eutrophied sandy sediments may substantially contribute to current marine N2 O emissions.